On the Governance of Public Pension Fund Management - Impavido, Gregorio (World Bank, Washington, DC, 2014)
The author surveys the empirical literature on the relationship between governance of public pension fund management and investment performance. He makes a preliminary attempt to identify good governance practices and distill governance guidelines aimed at reducing the political risk that is associated with central, public pension fund management. The author highlights the need for further work to support the development of a satisfactory set of governance guidelines.